BASIC ELEMENTS AND MECHANISM FOR REPRODUCING TECHNICAL POTENTIAL IN AGRICULTURE - UCHKUN ALIMOV; AZAMJON TULABOEV; AKMAL DURMANOV (International Journal of Innovations in Engineering Research and Technology, 2021)
Theoretical approaches and conceptsin specific spheres of the economy of the agro industrial complex are presented in the article. The concept is generated based on classic and modern economic theories. In addition, the necessity of basic elements and mechanism of reproduction of technical potential in agriculture of the Republic of Uzbekistan is proposed.